ผลของโปรแกรมการออกกำลังกายแบบผสมผสานต่อภาวะสุขภาพ สมรรถภาพทางกาย และความคาดหวังความสามารถตนเองของผู้สูงอายุ - Areeruk, Narisara; Rojpaisarnkit, Kunwadee; Wongprasit, Nawasanan (วารสารสาธารณสุข มหาวิทยาลัยบูรพา, 2015)
การวิจัยนี้เป็นการวิจัยกึ่งทดลอง มีวัตถุประสงค์เพื่อศึกษาผลของการออกกำลังกายแบบผสมผสานต่อภาวะสุขภาพ สมรรถภาพทางกาย และความคาดหวังความสามารถตนเองของผู้สูงอายุ โดยการเปรียบเทียบคะแนนเฉลี่ยของภาวะสุขภาพ สมรรถภาพทางกาย และความคาดหวังความสามารถตนเองของผู้สูงอายุก่อนและหลังการเข้าร่วมโปรแกรมการออกกำลังกายแบบผสมผสาน กลุ่มตัวอย่างได้แก่ผู้สูงอายุที่มีอายุระหว่าง 60-74 ปี อาศัยอยู่ในบ้านสุขสำราญ ตำบลหนองแวง อำเภอโคกสูง จังหวัดสระแก้ว จำนวน 45 คน ซึ่งเข้าร่วมโปรแกรมการออกกำลังกายแบบผสมผสานเป็นระยะเวลา 12 สัปดาห์ เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลคือ แบบสัมภาษณ์ข้อมูลส่วนบุคคลแบบสัมภาษณ์การรับรู้ความสามารถตนเองในการออกกำลังกาย แบบสัมภาษณ์ความคาดหวังในผลดีของการออกกำลังกาย แบบบันทึกภาวะสุขภาพและแบบบันทึกสมรรถภาพทางกาย วิเคราะห์ข้อมูลโดยใช้สถิติ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าที (Paired t-test)ผลการศึกษา พบว่าด้านภาวะสุขภาพ ผู้สูงอายุที่เข้าร่วมโปรแกรมการออกกำลังกายแบบผสมผสานมีค่าเฉลี่ยเส้นรอบเอวลดลงอย่างมีนัยสำคัญทางสถิติที่ระดับ.05 (t= 1.96, p=.05) ในขณะที่ความดันโลหิต ระดับน้ำตาลในเลือดและดัชนีมวลกายพบว่าไม่แตกต่างกัน ด้านสมรรถภาพทางกายผู้สูงอายุที่เข้าร่วมโปรแกรมการออกกำลังกายแบบผสมผสานมีค่าเฉลี่ยความแข็งแรงของกล้ามเนื้อแขน (t=5.18, p=.01) ความแข็งแรงของกล้ามเนื้อขา (t=6.30, p=.01) ความอ่อนตัวของร่างกายส่วนบน(t=3.80, p=.01) และความอ่อนตัวของร่างกายส่วนล่าง(t=4.52, p=.01) สูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ.05 ในขณะที่ความอดทนของร่างกาย และความคล่องตัวของร่างกายพบว่าไม่แตกต่างกัน ด้านความคาดหวังความสามารถตนเองในการออกกำลังกาย ผู้สูงอายุที่เข้าร่วมโปรแกรมการออกกำลังกายมีค่าเฉลี่ยการรับรู้ความสามารถตนเองในการออกกำลังกายสูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 (t=6.09, p=.00)ในขณะที่ความคาดหวังในผลดีของการออกกำลังกายแบบผสมผสานพบว่าไม่แตกต่างกัน The Effects of an Integrated Exercise Program on the Health Conditions, Physical Fitness, and Self-Efficacy Expectations of the Elderly The purpose of this quasi-experimental research was to investigate the effects of integrated exercises on the health conditions, physical fitness, and self-efficacy expectations of a group of elderly people by a means of a comparison on the average mean scores of their health conditions, physical fitness, and self-efficacy expectations. The sample consisted of 45 elderly people whose ages were between 60-74 years of age, and who were living in Ban Suksamran, Tambol Nongwanng, Amphoe Khok Sung, SaKeao Province. The people had participated in an integrated exercise program for 12 weeks. The tools used for data collection were the following: an interview format inquiring about personal data, the self-efficacy expectations about the integrated exercises, the expectations on the usefulness of the exercises, a health conditions field note, and a physical fitness field note. The collected data were statistically analyzed by using frequency, percentage, mean, standard deviation, and the Paired t–test. The results of this study indicated the following: 1) Concerning the aspect of health conditions, the elderly people who participated in the integrated exercise program had significant shorter waistlines at the .05 level (t=1.96, p=.05); however, their blood pressure, blood sugar level, and body mass indexes were not significant. 2) Concerning the aspect of physical fitness, the elderly people who participated in the integrated exercise program had significant higher average scores of arm strength (t=5.18, p=.01) and leg muscles strength (t=6.30, p=.01), and had a flexibility of the upper parts of their body (t=3.80, p=.01) and lower down parts of their bodies (t=4.52, p=.01). However, their body endurance and the balance of their bodies while moving was not significant. 3) Concerning the aspect of the self-efficacy expectations on the integrated exercises, the elderly people who participated in the program had significant higher average scores at the .05 level (t=6.09, p=.00); however, their expectations on the usefulness of the exercises were not significant.